(untitled) (Annals of Medical Research, 2024)
Aim: To investigate the effect of factor V Leiden mutation on neonatal and maternal morbidity and mortality in hypertensive pregnant groups. Materials and Methods: The study was carried out as a prospective case-controlled study with 108 pregnant women who applied to the Gynecology and Obstetrics Outpatient Clinic of Karadeniz Technical University, Faculty of Medicine within 2 years. Patients were divided into four groups: mild preeclampsia (n=20), severe preeclampsia (n=54), chronic hypertension (n=14), and normal pregnant women as a control group (n=20). Since superimposed preeclampsia (n=6), eclampsia (n=23), and HELLP syndrome (n=27) are variants of severe preeclampsia, these patients were included in the severe preeclampsia group. The clinical study aimed at investigating whether FVL mutation has any significant correlation with neonatal morbidity (IUGR, 1st and 5th minute < 7 Apgar score), intrauterine fetal death, neonatal mortality, maternal morbidity (ablatio placenta, deep vein thrombosis, intracranial hemorrhage, cesarean section rate) and mortality risk in hypertensive pregnant women. Results: Factor V Leiden mutation was most common in the severe preeclampsia group. Maternal and neonatal outcomes of pregnant women with and without FVL mutations were similar in all study groups (p > 0.05). Conclusion: Although FVL mutation was more common than usual in severe preeclamptic pregnant women, it did not affect maternal and neonatal outcomes. Prospective studies with larger patient populations investigating the effects of FVL mutation in preeclampsia are needed.